Menguji Peran Kapabilitas Dalam Meningkatkan Kinerja Usaha Mikro Kecil Dan Menengah (UMKM) - I Made Gede Ariestova Kurniawan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2020)
This research was conducted based on the different focus on the role of capability in improving the performance of MSMEs. In addition, there is also a research problem regarding the decline in the development of wet snack MSMEs in Denpasar City in 2019. This research was conducted on wet snack MSME entrepreneurs in Denpasar City with a total population and sample of 52 MSMEs. All data obtained from the questionnaire distribution is suitable for use, then analyzed using PLS 3.0. The results of the study suggest that entrepreneurial orientation has a positive and significant effect on capabilities, competence has a positive and significant effect on capabilities, marketing knowledge has a positive and significant effect on capabilities, entrepreneurial orientation has a positive and significant effect on the performance of MSMEs, competence has a positive and significant effect on the performance of MSMEs. Marketing knowledge has a positive and significant effect on MSME performance, capability has a positive and significant effect on MSME performance, entrepreneurial orientation has a positive and significant effect on MSME performance with capability as a mediating variable, competence has a positive and significant effect on MSME performance with capability as a mediating variable, marketing knowledge has a positive and significant effect on the performance of MSMEs with capability as a mediating variable. The implication of this research is that capability is able to mediate variables of entrepreneurial orientation, competence, marketing knowledge on the performance of MSMEs.